Obg-Like ATPase 1 Enhances Chemoresistance of Breast Cancer via Activation of TGF-β/Smad Axis Cascades - Liu, Jianzhou; Miao, Xiaoyu; Xiao, Bowen; Huang, Jing; Tao, Xufeng; Zhang, Jiong; Zhao, Hua; Pan, Yue; Wang, Hongwei; Gao, Ge; Xiao, Gary Guishan (Frontiers in Pharmacology, 2020)
Understanding the molecular mechanism of drug resistance helps identify an effective target for therapy of breast cancer. We investigated in this study the regulatory role of Obg-like ATPase 1 playing in multiple drug resistance of breast cancer. Paclitaxel resistant cell line (MCF-7-PTR) was developed by a continuous increasing paclitaxel concentration. MTT assay was used to validate either acquired resistant or OLA1 modified cell lines. qRT-PCR, immunoblot, apoptosis and cell cycle assays were performed to assess expression of genes and proteins in cell lines. A series of in vitro assays was performed in the cells with RNAi-mediated knockdown to elucidate the regulatory role of OLA1 in breast cancer. We demonstrated that OLA1 was highly correlated with either acquired or intrinsic resistance of breast cancer. Further study showed that escalated expression of OLA1 promoted EMT process in tumor cells through TGF-β/Smad signaling cascades, resulting in the enhanced expression of anti-apoptosis-related proteins (cleaved caspase3, Bax, Bcl-2) and the strengthen depolymerization of microtubules in tumor cells. Our findings revealed that OLA1 enhanced the anti-apoptotic ability and elucidated a regulatory role of OLA1 in promoting drug resistance of breast cancer. OLA1 is highly correlated with drug resistance of breast cancer. Chemo-sensitivity of the disease can be thus enhanced significantly by knocked down OLA1, which led to inactivation of the TGF-β/Smad signaling cascades, polymerized microtubules, and promoted cell apoptosis. Our data suggest that OLA1 may be developed as a potential target to improve chemotherapy of patients with breast cancer.